Endothelial expression of TGFβ type II receptor is required to maintain vascular integrity during postnatal development of the central nervous system. - Kathleen R Allinson; Hye Shin Lee; Marcus Fruttiger; Joseph H McCarty; Helen M Arthur (PLoS ONE)
TGFβ signalling in endothelial cells is important for angiogenesis in early embryonic development, but little is known about its role in early postnatal life. To address this we used a tamoxifen inducible Cre-LoxP strategy in neonatal mice to deplete the TypeII TGFβ receptor (Tgfbr2) specifically in endothelial cells. This resulted in multiple micro-haemorrhages, and glomeruloid-like vascular tufts throughout the cerebral cortices and hypothalamus of the brain as well as in retinal tissues. A detailed examination of the retinal defects in these mutants revealed that endothelial adherens and tight junctions were in place, pericytes were recruited and there was no failure of vascular smooth muscle differentiation. However, the deeper retinal plexus failed to form in these mutants and the angiogenic sprouts stalled in their progress towards the inner nuclear layer. Instead the leading endothelial cells formed glomerular tufts with associated smooth muscle cells. This evidence suggests that TGFβ signalling is not required for vessel maturation, but is essential for the organised migration of endothelial cells as they begin to enter the deeper layers of the retina. Thus, TGFβ signalling is essential in vascular endothelial cells for maintaining vascular integrity at the angiogenic front as it migrates into developing neural tissues in early postnatal life.